An Epidemiological Review of Sacrococcygeal Teratoma over Five Years in a Tertiary Care Hospital - Bedabrata, Mukhopadhyay; Chhanda, Das; Moumita, Sengupta; Kumar, Saha Ashis; Madhumita, Mukhopadhyay; Biswanath, Mukhopadhyay (Indian Journal of Medical and Paediatric Oncology, 2018)
Background: Teratoma refers to neoplasm containing at least two germ cell layers derivatives foreign to the site of origin. Sacrococcygeal teratoma is most common congenital tumor commonly present as an exophytic mass of varying size at coccyx. Aims and Objectives: (1) The aim is to find age, sex, and clinical presentation of cases of sacrococcygeal teratoma. (2) Application of American Academy of Pediatrics' surgical section classification and histological grading in all cases. Materials and Methods: A retrospective, observational study was conducted in the Department of Pathology in collaboration with the Department of Pediatric Surgery from February 2009 to January 2014. A total 13 cases of sacrococcygeal teratoma were included in the present study. The records of these patients were reviewed, and clinical profiles were noted. An average 12 slides were examined in each case to evaluate histological type and grades. Results: A retrospective study was conducted including thirteen cases of histologically confirmed sacrococcygeal teratoma over 5 years period. Male to female ratio was 1:2. As per as age distribution is concerned, 3 neonates (23%) presented with sacrococcygeal mass. Associated congenital malformation was seen in 2 cases (15.4%). According to the American Academy of Pediatrics (Altman's) classification, 23% of cases were Type I, 31% of cases patients Type II, 31% of cases Type III and 15% were for Type IV. The significant presacral component was noted in all malignant tumors. Conclusion: Two clinical patterns were observed in sacrococcygeal teratoma related to the age of presentation. As sacrococcygeal teratoma has potential to become malignant, meticulous search for the malignant component is required for histopathological categorization.
Keywords: Neuroepithelium; sacrococcygeal teratoma; Totipotential cell